Exchange rate pass-through under inflation targeting in transition economies - Marjan Petreski (Intereconomics, 2013)
This paper assesses whether the exchange rate pass-through in transition economies changed due to inflation targeting and the ongoing crisis. The economies of Central and South Eastern Europe and the Commonwealth of Independent States, of which nine are inflation targeters, are examined over the period 1993-2011. Results suggest that the exchange rate pass-through in transition economies is generally quite high. However, inflation targeters achieved a pass-through that was nearly four times lower and maintained it during the crisis due to their acquired monetary credibility. On the other hand, for non-inflation targeters, the pass-through increased during the crisis, likely due to temporary exchange rate shocks being perceived by agents as permanent.
Keywords: 330; Exchange Rate Pass-Through; Inflationssteuerung; Transformationsstaaten; Osteuropa; GUS-Staaten